Severe forms of food allergy - Emanuel Sarinho; Maria das Graças Moura Lins (Elsevier, 2017)
Objectives: To guide the diagnostic and therapeutic management of severe forms of food allergy. Data sources: Search in the Medline database using the terms "severe food allergy," "anaphylaxis and food allergy," "generalized urticaria and food allergy," and "food protein-induced enterocolitis syndrome" in the last ten years, searching in the title, abstract, or keyword fields. Summary of data: Food allergy can be serious and life-threatening. Milk, eggs, peanuts, nuts, walnuts, wheat, sesame seeds, shrimp, fish, and fruit can precipitate allergic emergencies. The severity of reactions will depend on associated cofactors such as age, drug use at the onset of the reaction, history and persistence of asthma and/or severe allergic rhinitis, history of previous anaphylaxis, exercise, and associated diseases. For generalized urticaria and anaphylaxis, intramuscular epinephrine is the first and fundamental treatment line. For the treatment in acute phase of food-induced enterocolitis syndrome in the emergency setting, prompt hydroelectrolytic replacement, administration of methylprednisolone and ondansetron IV are necessary. It is important to recommend to the patient with food allergy to maintain the exclusion diet, seek specialized follow-up and, in those who have anaphylaxis, to emphasize the need to carry epinephrine. Conclusion: Severe food allergy may occur in the form of anaphylaxis and food-protein-induced enterocolitis syndrome, which are increasingly observed in the pediatric emergency room; hence, pediatricians must be alert so they can provide the immediate diagnosis and treatment. Resumo: Objetivos: Abordar o manejo diagnóstico e terapêutico das formas graves de alergia alimentar. Fontes dos dados: Busca ativa na base de dados Medline dos te rmos "severe food allergies", "anaphylaxis and food allergy" e "food protein-induced enterocolitis" nos últimos dez anos e com busca nos campos título, resumo ou palavra-chave. Síntese dos dados: A alergia alimentar pode ser grave e ameaçadora à vida. Leite, ovo, amendoim, castanha, noz, trigo, gergelim, crustáceo, peixe e frutas podem precipitar emergências alérgicas. A gravidade das reações vai depender de fatores associados tais como idade, uso de medicamentos no início da reação, persistência de asma e/ou rinite alérgica grave, história de prévia anafilaxia, exercício e doenças intercorrentes. Para anafilaxia, a adrenalina intramuscular é uma indicação bem estabelecida. Para o tratamento da síndrome da enterocolite induzida pela proteína alimentar na fase aguda no setor de emergência, faz-se necessária a pronta reposição hidroeletrolítica, a administração de metilprednisolona e odansetrona IV. Importante recomendar ao paciente com o diagnóstico de alergia alimentar grave que mantenha a dieta de exclusão, procure acompanhamento especializado e, naqueles que apresentaram anafilaxia, enfatizar a necessidade de portar adrenalina. Conclusão: Alergia alimentar grave pode se manifestar como anafilaxia ou síndrome da enterocolite induzida por proteína alimentar em fase aguda as quais, por serem condições cada vez mais presentes e reconhecidas no setor de emergência pediátrica, demandam diagnóstico e tratamento imediatos. Keywords: Severe forms of food allergy, Food anaphylaxis, Food-protein-induced enterocolitis syndrome, Palavras-chave: Formas graves de alergia alimentar, Anafilaxia alimentar, Síndrome da enterocolite induzida pela proteína alimentar